Juízo e ação moral: desafios teóricos em psicologia - Souza, Leonardo Lemos De; Vasconcelos, Mario Sergio [UNESP] (Associação Brasileira de Psicologia Social, 2009)
The attending article presents and discusses the debate within the cognitive constructivist theories, which have as main representatives Jean Piaget and Lawrence Kohlberg. Such theories of rationalist and structuralist tradition maintain continuity between judgment and moral action and, at the same time, launch points of discussion on the complexity involved in the theme. New work fronts suggest the integration of other elements: culture, affectionateness, and the self, beyond the structures that may compound a referential that explains the relations between the aspects involved in moral behavior. Lastly, despite the criticism indicating a promising path in the search about judgment and moral action, considering its complex character, there are still limits in the making of the theoretical and methodological frameworks that articulate different perspectives of moral psychological analyses.

O presente artigo apresenta e discute a polêmica, no campo da psicologia moral, sobre as relações entre juízo e ação. Teorias de tradição racionalista e estruturalista, como as de Piaget e Kohlberg, afirmam uma relação de continuidade entre juízo e ação moral e, ao mesmo tempo, lançam pontos de discussão sobre a complexidade envolvida no tema. Por outro lado, novas frentes de trabalho sugerem a integração de outros elementos (a cultura, a afetividade e o self), além das estruturas que podem compor um referencial com o qual se evidenciem as relações entre os aspectos envolvidos nas condutas morais. Por fim, apesar das críticas acenarem com caminhos promissores na pesquisa sobre o juízo e a ação moral, ainda existem limites na construção de referenciais teóricos e metodológicos que articulem diferentes perspectivas de análise psicológica da moralidade.
Judgment and moral action: theoretic challenges in psychology
Keywords: moral; psychology; moral judgment; moral action; moral; psicologia; juízo moral; ação moral